Black Hole-Wormhole collisions and the emergence of islands - Rocha, J. V. (Gravity Sagas, 2023)
We use ray-tracing techniques to determine the evolution of the event horizon of a large black hole that "gobbles" a tiny, traversable wormhole. Our calculation is exact in the strict extreme mass ratio limit. The wormhole considered is described by the simple Ellis-Bronnikov spacetime, but the analysis can be reproduced for any desired spacetime for which one has the exact solution. Two setups are considered: a single-mouth wormhole connecting two otherwise independent universes, and a double-mouth wormhole within the same universe. In the first setting it turns out that, at early times, there exist two disconnected horizons —one in each universe— which then merge as the wormhole falls into the large black hole. In the second setup, we observe the appearance of an “island", a region of spacetime that is spatially disconnected from the exterior of the black hole, but in causal contact with future null infinity. The island shrinks as time evolves and eventually disappears, providing a communication channel with the interior of the large black hole for a certain duration. We compute numerically the lifetime of the island and verify that it grows linearly with the inter-mouth distance, to very good approximation.